Integrating Inquiry and Learning Community in Teaching Speaking: An Experimental Study - Sarinauli, Barep; Sabirin (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Language performance is the output of an individual’s language learning. In specific, speaking may serve as an indicator of students’ language skills. Second graders at a private secondary school, Maqamam Mahmuda, Takengon, Indonesia, had poor proficiency in this skill, particularly in English, with a median score of 34. The inefficient teaching and learning methods were to blame for this low achievement. As a result, it was proposed that a focused approach to the learning process be used. This study aims to determine whether integrating the inquiry and learning community may improve students’ English-speaking skills. It is expected to encourage students’ engagement in a learning group, predominantly speaking. In detail, the study focuses on how appropriately students perform in simple dialogue and monologues, and personal recounts following social function, general structure, and appropriate and contextual language elements. An experimental strategy using a one-group pretest and post-test design was employed to accomplish the study’s objective. Twenty pupils were randomly chosen as the treatment sample from a total population of 58 students. The outcome demonstrates that the students’ comprehension and pronunciation of English were significantly enhanced, from 34 to 60. The finding promotes the approach as a positive way to enhance students’ interest, comprehension, and confidence to speak in classroom interactions.